Combined or isolated transplantation of pancreas and kidney at the terminal stage of diabetic nephropathy - Malkhaz Viktorovich Kvaratskheliya (Сахарный диабет, 2010)
This review of current foreign literature is focused on the analysis of different variants of pancreas and kidney transplantation in patients with terminalrenal insufficiency resulting from diabetic nephropathy. Most authors consider combined pancreas and kidney transplantation to be the method ofchoice for patients with this pathology. Given the adequately functioning pancreas implant, this operation ensures excellent engaftment of the kidneyimplant and survival of the recipient. An alternative method is isolated transplantation of a kidney from a live donor with subsequent transplantationof the pancreas. Isolated transplantation of a cadaveric kidney results in transplant and recipient.